Effect of Hyperthyroidism Control During Pregnancy on Maternal and Fetal Outcome: A Systematic Review and Meta-Analysis - Alves Junior, Jose Mario; Bernardo, Wanderley Marques; Ward, Laura Sterian; Villagelin, Danilo (Frontiers in Endocrinology, 2022)
Context: Although treatment of overt hyperthyroidism during pregnancy is mandatory, unfortunately, few studies evaluated the impact of treatment reduction in maternal e fetal endpoints. Objective: This study aimed to assess the potential of reducing maternal-fetal effects with treating hyperthyroidism manifested during pregnancy through a systematic review with meta-analysis. Data Source: MEDLINE (PubMed), Embase, Cochrane Library Central, LILACS/BIREME until May 2021. Study Selection: Studies that compared, during the gestational period, women with hyperthyroidism treated versus euthyroid women. The following outcomes of this comparison were: pre-eclampsia, abruptio placentae, fetal growth retardation, gestational diabetes, postpartum hemorrhage, low birth weight, stillbirth, spontaneous abortions, premature birth. Data extraction: Two reviewers independently extracted data and performed quality assessments. Dichotomous data will be analyzed by computing risk differences (RD) with fixed- and random-effect models were employed according to the level of heterogeneity. Data Synthesis: Seven cohort studies were included. The results of the meta-analysis indicated that there was a lower incidence of preeclampsia (p=0.01), low birth weight (p=0.03), spontaneous abortion (p<0.00001), and preterm birth (p=0.001) in favor of the euthyroid pregnant group when compared to those who treated hyperthyroidism during pregnancy. Conclusions: Our findings demonstrated that treating overt hyperthyroidism in pregnancy is mandatory and appears to reduce some potential maternal-fetal complications, despite still there being a residual risk of negative outcomes.